Perbedaan Tekanan Darah Sebelum dan Sesudah Paparan Heat Stress pada Pekerja Perusahaan Industri Alumunium Yogyakarta - Zuhdan Marwanto; Erlina Marfianti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2011)
One source of danger in workplace is heat stress. Heat stress can cause changes in the cardiovascular system. The workload of heart will increase to regulate body temperature when body temperature rises due to exposure to heatstress. The objectives of this study were to find out the differences of blood pressure before and after exposure to heat stress on workers of Industrial Company Aluminium Yogyakarta. This study uses observational analytic methodwith cross sectional approach. The sample in this study that meets inclusion criteria is 25 people from two Industrial company Aluminium Yogyakarta (TS and ED). Data is collected by interview using a questionnaire to determine thecharacteristics of the respondents and measurements of heat stress, blood pressure in supine and standing position and axillary temperature. The statistical test performed using Wilcoxon match pair test with computer program. The average of heat stress in production section of Industrial Company TS Aluminium is 31.7 °C and ED Alumunium 32.6 °C. The average body temperature increased by 0.8 °C after exposure to heat stress (P <0,001). Systolic and diastolic blood pressure in supine and standing position decreased significantly after exposure to heat stress. Heat stress decreased systolic in supine (P<0,001) and standing (P<0.001) likewise diastolic in supine (P<0,001) and standing (P<0,001). Difference in systolic and diastolic blood pressure when changing body position prior heat stress compared to after heat stress no significant changes. Difference in systolic (P = 0.093) and difference in diastolic (P = 0.379). Based on this research, it can be concluded that there is significant differences in blood pressure before and after exposure to heat stress on workers of Industrial Company Aluminium Yogyakarta.